Hubungan karakteristik pria dewasa dengan biomarker sindroma metabolik - Refdanita, Refdanita; Damayanthi, Evy; Dwiriani, Cesilia Meti; Sumantri, Cece; Effendi, Adi Teruna (Jurnal Gizi dan Pangan, 2017)
The purpose of this study was to analyze the correlation characteristics of adult men aged 35-60 years with metabolic syndrome biomarkers. Cross-sectional study with a purposive sampling involving 36 adult men who have the criteria for metabolic syndrome according to International Diabetes Federation (IDF) 2006 was applied. The data was collected through interview and questionnaire administration. Body weight data measured using bathroom scale accuracy 0.1 kg, waist circumference with centimeter tape accuracy 0.1 cm, height with microtoice accuracy 0.1 cm. Serum lipid profiles were then analyzed by DSI kits Number 60111321 and 60111509, while the blood glucose was analyzed by DSI kit Number 60108392. The results were interpreted by using UV-Vis spectrophotometer. The results showed that most of subjects aged average 44.7±6.6 years, had BMI 30.3±4.2 kg/m2 and waist circumference 101.9±8.8 cm. Lipid profile of the subjects were serum triacylglycerol average 217.3 mg/dl, HDL-cholesterol 33.4 mg/dl, and fasting blood sugar  93.3 mg/dl. Body weight had a significant negative correlation with serum level of HDL (r=-0.34; p<0.05). A significant negative correlation also was found between age and triacylglycerol level (r=-0.44; p<0.01). Besides, a significantly positive correlation was found between age and serum level of HDL-cholesterol (r=0.33; p<0.05). There was no significant correlation on nutrient intake with metabolic syndrome biomarkers p≥0.05.  The research suggest the need to  regularly control weight and waist circumference to prevent metabolic syndrome.